Training of future teachers in the context of the development of Ukrainian pedagogical thought - Kapustina О. (Problems of Engineer-Pedagogical Education, 2023)
The article highlights the issue of training future teachers in the context of the development of Ukrainian pedagogical thought. It is emphasized that the standard of living and culture of a state directly depends on the knowledge and professional skills of its citizens, as well as their competitiveness and employability on the labor market. It is noted that the state is interested in solving this issue and supports innovative ideas regarding education and training. The author emphasizes the expediency of using the pedagogical experience of past generations and the scientific achievements of domestic researchers. The article substantiates the importance of studying the problem of the historical development of Ukrainian pedagogical thought in the process of training future teachers, given the need for society to study its own historical heritage, as well as the need to revive the ideas of the past regarding the methods and ways of organizing the educational process. The author concludes that strict requirements have always been placed on the personality of the teacher supposed to be a highly educated individual, have a broad worldview and analytical skills, creatively approach the solution of problems and issues that arise, love children and be a worthy citizen. The research paper examines the leading directions of the development of students and various aspects of their theoretical and practical training. Emphasis is placed on the relevance of the development of national and patriotic feelings, the enhancement of creative skills and environmental awareness at different times. The importance of self-improvement for the profession of a teacher is emphasized, as the teacher is an authority for a child and should be a model of spirituality, morality, and justice. The article also notes that the pedagogical field takes into account the process of informatization of society and supports the formation of teachers’ digital competence. The author analyzes the works of modern domestic researchers contributing to the development of Ukrainian pedagogical science. The methods, tools and ways of increasing the quality of vocational training of future teachers and educators are presented.